La atención pedagógica en los niños con discapacidad intelectual de 5 años de edad en la unidad educativa Lcdo. Carlos Vélez Verduga de la parroquia y cantón El Carmen provincia de Manabí - Rosado Valdez, Ana Lucia (2018)
The present investigation: "the pedagogical attention in the children with intellectual disability of 5 years of age in the educational unit" Lcdo. Carlos Vélez Verduga "of the parish and canton of El Carmen province of Manabí", is prioritized in the quality of attention that each of the children with different types of disabilities should receive, especially the intellectual one because it is characterized by significant limitations in the functioning intellectual and in the adopted behavior manifesting in social and practical conceptual skills. For this reason children must be integrated and included in the teaching-learning process, but not excluded without giving them the opportunity to learn at the pace that their potential allows……..